2022
DOI: 10.4103/jfmpc.jfmpc_1435_21
|View full text |Cite
|
Sign up to set email alerts
|

Review of the current literature on H syndrome treatment

Abstract: H syndrome is a systemic inherited autosomal recessive histiocytosis, with characteristic cutaneous findings accompanying systemic manifestations and a most common genetic mutation (OMIM 612391) as SLC29A3. The term “H Syndrome” is representative of presentation with hyperpigmentation, hypertrichosis, hepatosplenomegaly, heart anomalies, hearing loss, hypogonadism, low height, and, occasionally, hyperglycemia. H syndrome is new and growing entity in medicine. This syndrome is not specific to a region or a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The syndrome starts to manifest during the first decade of life, as in our patient, with sensorineural hearing loss, delayed growth, and/or cardiac anomalies [8]. Later on, during the first to second decades of life, hyperpigmented sclerodermatous changes start to appear, mainly covering the middle and lower body parts [1,2,7].…”
Section: Discussionmentioning
confidence: 56%
“…The syndrome starts to manifest during the first decade of life, as in our patient, with sensorineural hearing loss, delayed growth, and/or cardiac anomalies [8]. Later on, during the first to second decades of life, hyperpigmented sclerodermatous changes start to appear, mainly covering the middle and lower body parts [1,2,7].…”
Section: Discussionmentioning
confidence: 56%
“…According to recent reports, mycophenolate mofetil or tocilizumab medication may affect the course of the illness, leading to improvements in scleroderma-like skin lesions, arthritis, sensorineural deafness, and growth. The fact that these symptoms are affected by immunomodulatory medications is in line with their immune pathogenesis [5][6][7]. Anti-inflammatory medications, however, are frequently initiated many years after the onset of symptoms due to poor awareness of their rheumatological pertinence, making it challenging to assess their true efficacy in preventing illness-related organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…5 Clinical studies have revealed a range of manifestations, with some patients experiencing joint swelling, recurrent fever, hyperinflammation, and osteopenia. 5,6 Previous research indicates that hENT3 is crucial in facilitating mitochondrial and lysosomal functions, affecting cell proliferation and apoptosis. Elevated acute phase reactant values, similar to hyperinflammatory periodic fever syndrome, can be observed in patients with H syndrome.…”
Section: Introductionmentioning
confidence: 99%